Investigating the relationship between media multitasking and executive function within a military population - Scott Marriner; Julie Cantelon; Wade R. Elmore; Seth Elkin-Frankston; Nathan Ward (Cognitive Research)
Abstract The pervasive nature of media multitasking in the last fifteen years has sparked extensive research, revealing a nuanced but predominantly negative association with executive function. Given the cognitive demands and technological landscape of the modern battlefield, there is a critical interest in understanding how these findings may or may not extend to military members. To understand this relationship, we investigated the hypothesis that self-reported media multitasking behaviors would be negatively associated with performance-based measurements of executive function in a military population. Results found no significant relationship between overall media multitasking and any measures of executive function. However, average media multitaskers performed significantly better than heavy media multitaskers in a task-switching paradigm. Furthermore, we examined whether self-regulation moderated this relationship. Unlike previous research in non-military samples, we did not find that the impact of media multitasking on executive function was more pronounced among military members with lower self-regulation. By uncovering the nuanced interplay between these variables, this research contributes to a more thorough understanding of the cognitive implications of media multitasking both in general and within a military context.